Теоретичні засади українського націоналізму - Ленартович, Олег; Lenartovych, Oleh (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто теоретичні засади українського націоналізму періоду 1920–1930-х рр. Здійснено аналіз понятійного апарату, який має володіти науковець, що досліджує проблеми національно-визвольного руху. З’ясовано змістове навантаження термінів: нація, націоналізм, національно-визвольний рух, інтегральний націоналізм, чинний націоналізм. Визначено характер зовнішніх впливів на формування української теорії націоналізму.

In the article the theoretical founda¬tions of Ukrainian nationalism period 1920–1930’s conceptual apparatus that analyzes must possess researcher dealing with the problems of the national liberation movement. Defined terms semantic load-nation, nationalism, national liberation movement, integral nationalism, nationalism is valid. The character of external influences on the formation of Ukrainian nationalism theory. Each nation’s inherent nationalism. It creates a world in which the center of a national identity. It is manifested in daily life (use of native language, national service, promoting their own history, patriotic upbringing of children in the family), the creation of cultural and educational institutions, and finally, the creation of political parties. The desire to revive the Ukrainian nation state embodied in the creation of Ukrainian People’s Republic during the Revolution of 1917–1920, the armed struggle UPA during the Second World War, the activities of dissidents and others. Thus, the proposed issues is relevant because it provides an opportunity to understand the ideological foundations of the national liberation struggle, the ultimate goal and the means to achieve it.
Theoretical Foundations of Ukrainian Nationalism
Keywords: нація; націоналізм; національно-визвольний рух; інтегральний націоналізм; nation; nationalism; national-liberation movement; integral nationalism